2021
DOI: 10.1128/spectrum.01377-21
|View full text |Cite
|
Sign up to set email alerts
|

Listeria monocytogenes Sublethal Injury and Viable-but-Nonculturable State Induced by Acidic Conditions and Disinfectants

Abstract: Sublethally injured and VBNC cells may evade detection, resulting in underestimation of a food product’s microbial load. Under favorable conditions, cells may regain their growth capacity and acquire new resistant characteristics, posing a major threat for public health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 57 publications
2
8
0
Order By: Relevance
“…However, recommended concentrations of peroxyacetic acid (PAA, 80 mg/L) and chlorine dioxide (ClO 2 , 3 mg/L) reduced the levels of culturable pathogenic bacteria but induced the VBNC state of the remaining cells. Similarly, Arvaniti et al (2021) showed that PAA had a milder effect than sodium hypochlorite, inducing sublethal injury and it also allowed cellular recovery following 1 min of exposure to 40 mg/L. This is also consistent with the observations by Gu et al (2020), who reported that incubation for 30 s in 30 mg/L PAA resulted in undetectable population levels of L. monocytogenes by selective plating.…”
Section: Impact Of Different Water Disinfection Treatments On the Ind...supporting
confidence: 86%
See 1 more Smart Citation
“…However, recommended concentrations of peroxyacetic acid (PAA, 80 mg/L) and chlorine dioxide (ClO 2 , 3 mg/L) reduced the levels of culturable pathogenic bacteria but induced the VBNC state of the remaining cells. Similarly, Arvaniti et al (2021) showed that PAA had a milder effect than sodium hypochlorite, inducing sublethal injury and it also allowed cellular recovery following 1 min of exposure to 40 mg/L. This is also consistent with the observations by Gu et al (2020), who reported that incubation for 30 s in 30 mg/L PAA resulted in undetectable population levels of L. monocytogenes by selective plating.…”
Section: Impact Of Different Water Disinfection Treatments On the Ind...supporting
confidence: 86%
“…This antimicrobial tolerance is associated with physiological changes that may be stochastic or environmentally induced as opposed to mutational events leading to non‐reversible resistance (Ayrapetyan et al., 2018). In fact, exposure of bacterial cells to sub‐lethal stressors may induce both, sublethal injury (persistent cells) and the VBNC state (Arvaniti et al., 2021). Several authors support the hypothesis that persistence and VBNC cells are related and part of a ‘dormancy continuum’, in which they share similar mechanisms but are found in different physiological positions on the dormancy range (Ayrapetyan et al., 2015a).…”
Section: Assessmentmentioning
confidence: 99%
“…2C ). These cells resembled the viable but nonculturable (VBNC) phenotype: cells that do not divide in the presence of antibiotics (or other stressors ( 44 , 48 , 49 )) or after their removal ( 16 , 18 , 36 , 37 , 47 , 50 , 51 ). In our experiments, cells resembling the VBNC phenotype did not elongate during the treatment with antibiotics or within the 21 h of incubation in LB medium post-antibiotic exposure ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…VBNC cells would thus be in a deeper dormant state than persister cells (Ayrapetyan et al, 2018). A recent study suggests that sublethal injury is also an initial stage of dormancy that is followed by the VBNC state (Arvaniti et al, 2021). It can be pointed out that VBNC cell subpopulations can also exist naturally in unstressed environments, as the result of a stochastic physiological phenomenon, which leads to a bacterial pool predisposed to resist potential future stresses (Ayrapetyan et al, 2015;Goncalves and De Carvalho, 2016).…”
Section: Overview Of the Vbnc Statementioning
confidence: 99%
“…Treatments with lower concentrations of chlorine or benzalkonium chloride also show induction of VBNC Lm (Afari and Hung, 2018;Noll et al, 2020;Truchado et al, 2020). VBNC Lm also emerged in presence of other antimicrobial agents, such as surfactants (Robben et al, 2018), preservatives (Zolfaghari et al, 2020), essential oils (De Medeiros Barbosa et al, 2020) or peracetic acid (Gu et al, 2020;Arvaniti et al, 2021). Chiara et al (2021) interestingly showed that the origin of the bacterial cells has a significant impact on the viability and culturability of Lm against antimicrobial treatments.…”
Section: Induction Of the Vbnc State Of Lm By Exposure To Antimicrobi...mentioning
confidence: 99%